PENGARUH PROMOSI MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN DENGAN VIRAL MARKETTING SEBAGAI VARIABEL INTERVENING ( STUDI PADA KONSUMEN WARUNG SIJI HOUSE AND RESTO MALANG ) - Failatul Khoiro; N Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT This study aims to determine the effect of social media promotion on purchasing decisions with viral marking as an intervening variable. The research population is Warung Siji House and Resto with a total of 700 consumers. The sample in this study were 88 respondents. Data collection is done by distributing questionnaires. Analysis of the data used in this study using validity, reliability, normality, path analysis, t test and sobel testhe results showed that social media promotion had no significant effect on purchasing decisions, social media promotion had a significantly positive effect on Viral marketing, Viral marketing had a significant positive effect on purchasing decisions. Promotion through social media has a significant positive effect on purchasing decisions mediated by viral marketing at consumers of Warung Siji House And Resto Malang keywords: social media promotion, purchasing decisions, viral marketing